2022
DOI: 10.1002/anie.202208189
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Walled Carbon Nanotubes Encapsulated within Metallacycles

Abstract: Mechanically interlocked derivatives of carbon nanotubes (MINTs) are interesting nanotube products since they show high stability without altering the carbon nanotube structure. So far, MINTs have been synthesized using ring‐closing metathesis, disulfide exchange reaction, H‐bonding or direct threading with macrocycles. Here, we describe the encapsulation of single‐walled carbon nanotubes within a palladium‐based metallosquare. The formation of MINTs was confirmed by a variety of techniques, including high‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…To illustrate the capabilities of the algorithm, we present the results obtained using this tool for the analysis and comparison of mechanically interlocked carbon nanotubes (MINTs) [56][57][58][59][60][61][62][63] and the pristine 6,5-SWNT used for their preparation. In particular, mechanical bonds are used to anchor Cu 2+ metalloporphyrin dimeric rings around carbon nanotubes to form magnetic cooper MINTs (Cu-mMINTs), as reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the capabilities of the algorithm, we present the results obtained using this tool for the analysis and comparison of mechanically interlocked carbon nanotubes (MINTs) [56][57][58][59][60][61][62][63] and the pristine 6,5-SWNT used for their preparation. In particular, mechanical bonds are used to anchor Cu 2+ metalloporphyrin dimeric rings around carbon nanotubes to form magnetic cooper MINTs (Cu-mMINTs), as reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…6c and d). 62 In this case, the coordination is based on N-heterocyclic carbene ligands and Pd metal centres. In line with the results reported by the team led by Komatsu, we also found that the formation of MINTs was very sensitive to the size complementarity between the cavity of the macrocycle and the diameter of the SWNT.…”
Section: Making Mintsmentioning
confidence: 99%
“…Mechanically interlocked molecules (MIMs) are a type of compounds constituted by components which are bonded together through noncovalent interactions, forming a mechanical bond. [1][2][3] Within the range of intertwined compounds, rotaxanes are postulated as ideal candidates for the design of molecular machines, developing applications in a wide range of fields, [4][5][6] such as catalysis, [7][8][9][10][11][12][13][14] materials science [15][16][17][18][19][20][21][22][23][24] or medicinal chemistry. [25][26][27] Usually, the design of these structures seeks the stability of the mechanical bond, thus preventing the dissociation of the different components in order to carry out a specific function.…”
Section: Introductionmentioning
confidence: 99%